IMPLEMENTASI KAIDAH-KAIDAH ISLAM DALAM PENGELOLAAN ZAKAT PROFESI - SUTARDI SUTARDI; MUHAMMAD IRWAN; IHSAN RO’IS (Prodi Manaj. Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam – UIN Imam Bonjol Padang, 2017)
The theme of the article is the banks and financial institutions. This study aims to determine the implementation of Islamic rules in the management of